Pengaruh Leverage, Operating Capacity, Firm Size, dan Operating Cash Flow Terhadap Financial Distress - Hwang, Helvina; Viriany, Viriany (GEMA EKONOMI, 2023)
This study aims to determine the effect of liquidity, leverage, investment opportunity set, and firm size on the earning quality of plastic and packaging manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. There are 19 plastic dan packaging manufacturing companies in the population tested in this study and the non-probability sampling technique (purposive sampling) is taken in choosing the samples by applying several criterias. The sample data used in 48 data with a total of 12 companies in the period of 2020-2022. The data will be processed using SPSS ver.25. In this study, a classical assumption test and multiple linear regression method were carried out. This research shows that Liquidity, Leverage and Investment Opportunity Set have no significant effect on Earnings Quality. On the other hand, Firm Size has a negative significant effect on Earnings Quality.